Treatment of AIDS Encephalopathy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
A 3-year old boy who had acquired HIV infection transplacentally and developed AIDS encephalopathy is reported from the Depts of Paediatrics and Immunology, Newcastle General Hospital, Newcastle upon Tyne, England.